Editorial: Inaugurating the Journal of Animal Rights Law: Collective reflections on the future of animal rights law - Lercier, Marine; Kurki, Visa; Fernandez, Angela; Winders, Delcianna; Tischler, Joyce; Favre, David; Wadiwel, Dinesh; Deckha, Maneesha; Liebman, Matthew; Fasel, Raffael; Schaffner, Joan; P. Wilson, Amy; et al. (Journal of Animal Rights Law, 2025)
This editorial inaugurates the Journal of Animal Rights Law with collective reflections from leading scholars in the field. Contributors trace the historical roots and future horizons of animal rights law, assess current challenges and opportunities, and welcome the journal as a forum for rigorous scholarship and inquiry. They outline priority areas for further research and legal reform, weigh reasons for hope and concern across jurisdictions, and call for greater inclusivity and frameworks that support coexistence with non-human animals. While the task ahead is formidable, the contributors emphasise the scale of the collective potential for change, and what we can accomplish together.